¿Ideales cosmopolitas? Del reino de la libertad a la asunción de la necesidad. Los desafíos de una lectura feminista de cara al sur - Ciriza, Alejandra (Pontificia Universidad Católica del Perú, 2024)
Under the conjecture that embodied people draw expectations of emancipation on the basis of a certain historical horizon, this work investigates the limits and pressures that the current conditions of existence imprint on the political imagination of those who inhabit the south of the planet, at a time of increase in inequalities between human beings and aggression against the nature that we are and in which we live. This work traces, from a situated and feminist perspective, some significant temporal milestones because these marks in time account made possible a cosmopolitan horizon, in which we can take notice that the world with which we stay, in which we live, is one.  Under the sign of the French Revolution, Kant constructed the idea of a cosmopolitan government and imagined a norm for regulating relations between states that would enable a hospitality capable of welcoming the stranger as a full subject of law. Under the imprint of 1848 (and also of 1871) Marx projected, from the terrain of history and class struggle, the possibility of an emancipation that could be international. The world today shows a desolate panorama: the globalization of the world with its aftermath of reification and commodification of nature, with the bet on war in its different versions as a way out of the capitalist crisis, with fierce competition for what has become scarce: fuel, land, water, seeds. Cosmopolitanism, as an ethical and political imperative, invites us to take on the challenge implied by the impossibility of reproducing life on the planet under the current conditions of capitalist globalization. The cosmopolitan horizon can no longer be the realm of abstract freedom, but that of the assumption of the determinations of the realm of necessity: dependence on the nature that we are and in which we live, the importance of the body, the need for food, affection, care that human been can only satisfy in community.

Bajo la conjetura de que las personas encarnadas dibujan las expectativas de emancipación sobre la base de un cierto horizonte histórico, este trabajo indaga por los límites y las presiones que las actuales condiciones de existencia imprimen sobre la imaginación política de quienes habitamos al sur del planeta, en un momento de aumento de las desigualdades entre seres humanos y de brutal agresión sobre la naturaleza que somos y en la cual vivimos. Este trabajo recorre, desde una perspectiva ubicada y feminista, algunos hitos temporales significativos pues esas marcas en el tiempo dan cuenta de momentos que hicieron posible un horizonte cosmopolita, en los cuales se pudo advertir hasta qué punto el mundo con el que nos hallamos, en el que vivimos, es uno. Bajo el signo de la Revolución francesa, Kant construyó la idea de un gobierno cosmopolita e imaginó una norma de regulación de las relaciones entre los Estados que habilitara una hospitalidad capaz de acoger al extranjero como sujeto pleno de derecho. Bajo la impronta de 1848 (y también de 1871) Marx proyectaba, desde el terreno de la historia y de la lucha de clases, la posibilidad de una emancipación que no podía sino ser internacional. El mundo muestra hoy un panorama desolador: la globalización del mundo con sus secuelas de cosificación y mercantilización de la naturaleza, con la apuesta a la guerra en sus distintas versiones como salida a la crisis capitalista, con la competencia feroz por lo que ha devenido escaso: los combustibles, la tierra, el agua, las semillas. El cosmopolitismo, como imperativo ético y político, nos invita a asumir el desafío que implica la imposibilidad de reproducción de la vida en el planeta bajo las actuales condiciones de globalización capitalista. El horizonte cosmopolita ya no puede ser el reino de la libertad abstracta, sino el de la asunción de las determinaciones del reino de la necesidad: la dependencia de la naturaleza que somos y en la cual vivimos, la importancia del cuerpo, la necesidad de alimento, afecto, cuidado que las personas solo podemos satisfacer en comunidad.
Cosmopolitan ideals? From the Reign of Liberty to the assumption of necessity. A Feminist Reading from the South
Keywords: Cosmopolitan Ideals; Political Imagination; The Reign of Liberty /The Reign of Necessity; Southern Feminisms; Ideales cosmopolitas; Imaginación política; Reino de la libertad/reino de la necesidad; Feminismos del sur; https://purl.org/pe-repo/ocde/ford#2.07.01